'It is your duty to be human' : a few theological remarks amidst the HIV / AIDS-crisis : the challenge of HIV / AIDS to Christian theology - Naude, Piet (Scriptura : Journal for Contextual Hermeneutics in Southern Africa, 2005)
This paper first explains why the HIV / Aids pandemic requires a fundamental reorientation of our theological reflection, followed by three reasons why such reflection is inhibited in the present churches' context. It then attempts to set out how God the creator; Jesus, the self-donating priest; and the Holy Spirit create the basis for the church as healing and embracing community.
Free